159k views
0 votes
If f(x) = 5x – 2 and g(x) = 2x + 1, find (f - g)(x).

A. 3 - 3x
B. 3x-3
C. 7x-1
D. 7x-3

1 Answer

3 votes

Answer:

The difference of the functions is (f-g)(x) = 3x - 3

Explanation:

In the problem, we are asked to find the difference of the two functions, f(x) and g(x). When we see (f-g)(x), this means that we are going to subtract g(x) from f(x).

f(x) = 5x - 2

g(x) = 2x + 1

(f-g)(x) = (5x - 2) - (2x + 1)

Distribute the negative to (2x + 1)

(f-g)(x) = 5x - 2 - 2x - 1

Combine like terms. Make sure your answer is in standard form.

(f-g)(x) = 3x - 3

So, the answer to the equation is (f-g)(x) = 3x - 3

User Simone Sanfratello
by
5.1k points